The Effect of Positive Emotions as a Moderation on the Influence of Store Atmosphere and Hedonic Shopping on Impulse Buying : At Miniso Lippo Cikarang - Retno Wulandari; Daru Asih (Journal of Management and Informatics, 2024)
The retail business is growing very rapidly as a result of changes in modern society's lifestyle. Impulsive purchases account for the majority of sales in the modern retail industry. This research aims to examine the effect of positive emotions as a moderation on the influence of store atmosphere and hedonic shopping on impulse buying among Miniso Lippo Cikarang consumers with a sample of 177 respondents. This research uses SOR theory and quantitative methods with non-probability sampling techniques. Test data is carried out with Smart PLS. The research results show that store atmosphere has a positive and significant effect on impulse buying, as well as hedonic shopping and positive emotions having a positive and significant effect on impulse buying. Positive emotions have been proven to strongly moderate the influence of store atmosphere and hedonic shopping on impulse buying.